Report of a Case of Steroid-Induced Psychosis and Inappropriate Sexual Behaviour in an Adolescent - Demir, T.; Karacetin, G.; Dogangun, B.; Kocabasoglu, N. (Pharmacopsychiatry, 2012)
We present the case of an acute steroid-induced psychosis in a 17-year-old boy who presented with inappropriate sexual behaviour. Quetiapine treatment was initiated at an initial dosage of 300 mg/day. The dosage was increased to 900 mg/day on the fourth day of the treatment. The patient’s symptoms began to improve in the second week and were resolved by the fourth week of quetiapine treatment. Steroid use may result in a psychosis, including inappropriate sexual behaviour. Clinicians should be very cautious while administering these drugs and should consider and monitor side effects carefully.
Keywords: antipsychotic drugs; adverse effects; psychosis